Comparison of Time and Accuracy of Transaction Recording Using Microsoft Excel and ABSS Accounting: A Simulation Study on a Simple Trading Business - Arif Rahman Hasdik (Phinisi Applied Accounting Journal, 2026)
This study aims to compare the time efficiency and accuracy level of transaction recording using Microsoft Excel and ABSS Accounting in a simple trading business simulation. The study employed a descriptive quantitative approach with a simulation method. The research data were obtained through a simulation of recording 20 stationery trading business transactions consisting of 10 cash sales transactions, 5 inventory purchase transactions, and 5 accounts payable payment transactions. The recording process was carried out using Microsoft Excel 2019 and ABSS Accounting v25 trial. Measurements were conducted on transaction recording time, initial setup time, and the number of errors that occurred during the recording process. The simulation was conducted three times to obtain more consistent average results.The results showed that ABSS Accounting had a higher level of efficiency compared to Microsoft Excel. The average recording time using ABSS Accounting was 7 minutes and 2 seconds, while Microsoft Excel required an average of 12 minutes and 8 seconds. In terms of accuracy, the use of ABSS Accounting produced no errors, whereas Microsoft Excel resulted in three errors consisting of two formula reference errors and one transaction amount input typo. The findings indicate that automation systems and account validation features in accounting software are able to accelerate the recording process while reducing the risk of human error compared to manual spreadsheet-based recording. Nevertheless, Microsoft Excel still has advantages in terms of flexibility of use and does not require an initial setup before being used. This study is expected to serve as a reference for business owners and accounting educators in determining a transaction recording system that suits operational business needs.